Fibre Distribution and Dosage Performance on the Impact Resistance of Oil Palm Shells Concrete with Hybrid Polypropylene Fibre-Mesh - Muda Z.C.; Hafez M.; Syamsir A.; Zahari E.S.; Alam M.A.; As?ad Z. (Natural Sciences Publishing, 2025)
This research paper investigates the effect of top and bottom fibre distribution configurations against 1%, 2%, and 3% fibre volume fractions on the impact performance of lightweight oil palm shells concrete slabs with polypropylene fibres and polypropylene mesh under low-velocity impact projectile. Lightweight aggregate in concrete utilizing agricultural waste recycling materials has been used to produce a green product for the construction industry to prevent environmental pollution. Slabs of dimensions 300mm x 300mm and 40mm thickness are subjected to a drop-weight impact test using a self-fabricated rig and a 1.05 kg steel ball dropped from a height of 0.57 m. The study?s main objectives are to analyze the relationship between impact energy and crack resistance against fibre volume fractions for top and bottom fibre distribution. The results indicate that the bottom fibre distribution outperforms the top fibre distribution in all the impact-related factors. An increase in PP fibre dosage leads to significant improvements in the impact behaviour of the slabs. Bi-linear equations were proposed for top and bottom fibre distribution between service and ultimate impact behaviour against fibre volume fraction. The top fibre distribution has more segmental failure zones than the bottom fibre; however, the bottom fibre distribution has better impact performance and post-cracking ductility. PP fibres control the micro-cracks at the initial phase, while the PP mesh bridges the minor cracks at the failure phase. ? 2024 NSP Natural Sciences Publishing Cor.